Applying cold sintering process to a proton electrolyte material: CsH2PO4. Issue 2 (February 2019) - Nakaya, Hiroto; Iwasaki, Masato; de Beauvoir, Thomas Herisson; Randall, Clive A.
Abstract: The Cold Sintering Process (CSP) was applied to CsH2 PO4, a proton conducting electrolyte. The powders were sintered between 120 °C and 200 °C under 300 MPa for 1 h and the ceramics investigated for their respective structure-property-process relations. The microstructure development of the CsH2 PO4 materials was characterized for grain size, and dihedral angle distributions for a variety of the CSP processing conditions. The electrical properties of the cold sintered CsH2 PO4 were characterized through electrochemical impedance spectroscopy over a temperature range between 120 °C and 200 °C. The data suggests that the proton conductivity is 2.30 × 10 −4 Scm -1 at 200 °C with good repeatability during cycled measurements.